The evolving role of cholesteryl ester transfer protein inhibition beyond cardiovascular disease - Nehal Mehta; Katerina Dangas; Marc Ditmarsch; Patrick C.N. Rensen; Mary R. Dicklin; John J.P. Kastelein (Elsevier, 2023)
The main role of cholesteryl ester transfer protein (CETP) is the transfer of cholesteryl esters and triglycerides between high-density lipoprotein (HDL) particles and triglyceride-rich lipoprotein and low-density lipoprotein (LDL) particles. There is a long history of investigations regarding the inhibition of CETP as a target for reducing major adverse cardiovascular events. Initially, the potential effect on cardiovascular events of CETP inhibitors was hypothesized to be mediated by their ability to increase HDL cholesterol, but, based on evidence from anacetrapib and the newest CETP inhibitor, obicetrapib, it is now understood to be primarily due to reducing LDL cholesterol and apolipoprotein B. Nevertheless, evidence is also mounting that other roles of HDL, including its promotion of cholesterol efflux, as well as its apolipoprotein composition and anti-inflammatory, anti-oxidative, and anti-diabetic properties, may play important roles in several diseases beyond cardiovascular disease, including, but not limited to, Alzheimer's disease, diabetes, and sepsis. Furthermore, although Mendelian randomization analyses suggested that higher HDL cholesterol is associated with increased risk of age-related macular degeneration (AMD), excess risk of AMD was absent in all CETP inhibitor randomized controlled trial data comprising over 70,000 patients. In fact, certain HDL subclasses may, in contrast, be beneficial for treating the retinal cholesterol accumulation that occurs with AMD. This review describes the latest biological evidence regarding the relationship between HDL and CETP inhibition for Alzheimer's disease, type 2 diabetes mellitus, sepsis, and AMD.